Protocol registration: Review Title: The role of place in Australian Aboriginal Community Controlled Organisations: A scoping review into health and wellbeing interventions for Indigenous Australian adults - Fiona Sheppeard (10725834); Peter Kelly (11101522); Georgia Stewart (11101526); Bronwyn Fredericks (9352292); Kathleen Clapham (11101535) (2021)
This is a protocol registration for a scoping review I am currently conducting. This scoping review focuses on examining how place is incoporated into mental health and social and emotional wellbeing approaches that are delivered by Aboriginal Community Controlled Organisations.